2012
DOI: 10.1186/1472-6920-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Student apathy for classroom learning and need of repositioning in present andragogy in Indian dental schools

Abstract: BackgroundIn the world of technology, when today's student is approaching the on-line /distance learning in the open universities and doing on-line self-assessment, the classroom learning is vanishing slowly. Globally, teachers are taking efforts to improve the pedagogy by implementing effective methods to retain the classroom teaching and student attendance. The present study aims at shedding some light on the need of changing the adult education strategies (andragogy), which can effectively improve the stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…In addition, the application of online learning in the context of COVID 19 has helped lecturers improve their ability to teach online to students. This is consistent with a previous study that found instructors have experience in learning because they are trained and have a clear plan to teach students (Dable et al, 2012). In addition, e-learning has provided an essential context for repositioning how tutorials and lectures can be used as the basis for collaborative learning between students and faculty (Freeze et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the application of online learning in the context of COVID 19 has helped lecturers improve their ability to teach online to students. This is consistent with a previous study that found instructors have experience in learning because they are trained and have a clear plan to teach students (Dable et al, 2012). In addition, e-learning has provided an essential context for repositioning how tutorials and lectures can be used as the basis for collaborative learning between students and faculty (Freeze et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Learning outcomes are a key factor for the development inspection, which is the indicator by which learning outcomes of students are judged ( Guay et al, 2008 ), and even the element of students’ learning evaluation and school’s satisfaction ( Peterson and Einarson, 2001 ; Duque and Weeks, 2010 ; Sergis et al, 2018 ). Pike et al (2011 , 2012) pointed out that learning is a process that arises from actions taken based on experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The need for an innovative curriculum has been continuously highlighted in many studies [15,[46][47][48]9]. There are some recommended elements to accomplish the implementation in limited resources settings:…”
Section: Discussionmentioning
confidence: 99%